Towards a more holistic understanding of child participation: Foregrounding the experiences of children in Ghana and Nigeria. (May 2020) - Twum-Danso Imoh, Afua; Okyere, Samuel
Highlights: The focus on voice-oriented child participation has led to a discourse which is one dimensional. In contrast, children in the study sites viewed child participation in more holistic terms. Many viewed the concept as being closely intertwined with the notion of responsibility. For many these responsibilities enhanced their recognition within their families. These views must be situated within the broader social and cultural contexts of these societies. Abstract: Concerns about the absence of children's voices from matters affecting their lives and their societies have informed the emergence, construction and hegemony of 'child participation as voice' in global children's rights debates, policies and practices since the adoption of the United Nations Convention on the Rights of the Child (UNCRC) in 1989. While this voice-oriented participation construct has some merit, this paper argues that it is also limiting and unrepresentative of the diverse ways in which children participate or seek representation and inclusion in different political, social and economic contexts. The paper draws on findings from research studies in Nigeria and Ghana to buttress this argument and concludes with a call to go beyond the participation-as-voice orthodoxy and instead, move towards participatory practices which are better aligned with the meanings children themselves attach to their everyday lives and to the key personal and social relationships that they value.